Sport Specialization Classification and Injury Risk in Female Athletes. (November 2022) - Okoruwa, Ehiamen T.; Abbott, Alexandra; Stamm, Michaela; Mulcahey, Mary K.
Background: Description of possible detrimental effects of sport specialization specific to adolescent female athletes is limited in current literature with no consensus on sport specialization classification. Hypothesis: Specialized female athletes will have higher rates of injury, body image issues, and menstrual dysfunction, regardless of the specialization classification utilized. Study Design: Cross-sectional. Level of Evidence: Level 3. Methods: Retrospective data was obtained from questionnaires from female athletes in local high schools (n = 229; 13–18 years of age). The 3-point specialization scale was used to analyze differences in injury rates, body image issues, and menstrual dysfunction within low, moderate, and highly specialized athletes. When comparing accuracy of specialization scales in identifying high risk athletes, three peer-reviewed specialization classification scales were utilized—a 3-point scale, a 6-point scale, and a binary self-selection scale. Odds ratios (OR) and 95% confidence intervals (CI) were calculated for studied variables (a priori p ≤ 0.05). Results: Of 229 athletes surveyed, 219 (95.6%) completed the 3-point specialization classification questions and were included in the study. 91 athletes (41.6%) were categorized as low specialization (LS), 59 (26.9%) were moderately specialized (ModS), and 69 (31.5%) were highly specialized (HS). ModS athletes were more likely to have a history of stress fractures (SFx) compared to LS athletes ( p = 0.02; OR 3.62; 95% CI 1.27–10.26). Compared to LS athletes, HS athletes were more likely to have injury history ( p = 0.01; OR 2.93; 95% CI 1.38–6.24) and a history of concussion ( p < 0.01; OR 5.00; 95% CI 1.86–13.42). Conclusion: Among female high school athletes, higher levels of specialization are associated with greater risk of injuries overall, and greater risk of concussions and SFx. This study did not demonstrate significant associations between specialization and body image issues or menstrual dysfunction. Clinical Relevance: This study further strengthens the association between injury and sport specialization and suggests that combining specialization scales better improves risk stratification which overall aids in preventing athlete injury.